Pengaruh Islamic Corporate Governance Terhadap Maqasid Syariah Index dengan Firm Size dan Firm Age sebagai Variabel Kontrol: (Studi pada Perbankan Syariah yang Terdatar di Otoritas Jasa Keuangan) - Meisya Surya Islami; Chara Pratami T Tubarat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the influence of Islamic Corporate Governance on the performance of Maqasid Shariah in Islamic Commercial Banks in Indonesia. The performance of Maqasid Shariah is measured using the Maqasid Shariah Index, which consists of three main dimensions: educating individuals, establishing justice, and promoting public interest. The independent variables in this study include components of Islamic Corporate Governance, namely the Board of Commissioners, the Sharia Supervisory Board, and Independent Commissioners. Firm size and firm age are employed as control variables. The study uses a sample of Islamic Commercial Banks in Indonesia that are registered with the Financial Services Authority (OJK) during the period of 2021–2023, with a total of 33 data observations. Data analysis was conducted using panel data regression with the Stata 17 application. The results indicate that the Board of Commissioners and Independent Commissioners do not have a significant effect on Maqasid Shariah performance, while the Sharia Supervisory Board has a significant negative effect on the Maqasid Shariah performance of Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK).